DBP-induced endoplasmic reticulum stress in male germ cells causes autophagy, which has a cytoprotective role against apoptosis in vitro and in vivo. (14th March 2016) - Zhang, Guowei; Liu, Kaijun; Ling, Xi; Wang, Zhi; Zou, Peng; Wang, Xiaogang; Gao, Jianfang; Yin, Li; Zhang, Xi; Liu, Jinyi; Ao, Lin; Cao, Jia
Graphical abstract: Highlights: DBP exposure induced apoptosis both in vitro, in GC-2 cells, and in vivo, in prepubertal rat testis germ cells. DBP induced ER stress in germ cells both in vitro and in vivo. ER stress-mediated CHOP activation contributed to DBP-induced germ cell apoptosis. DBP-induced ER stress also triggered autophagy, which has a protective effect against germ cell death. Abstract: Recently, spermatogenic cell apoptosis was shown to play a key role in the induction of testicular atrophy by dibutyl phthalate (DBP), thus causing reproductive toxicology. However, the molecular events induced by DBP in apoptotic germ cells remain unclear. In the present study, the mouse spermatocyte-derived GC-2 cell line was exposed to different doses of DBP. We found that DBP induced marked apoptosis in GC-2 cells. The levels of the major endoplasmic reticulum (ER) stress markers GRP-78, ATF-6, and p-EIF2α were elevated when GC-2 cells were exposed to 25 μM DBP and increased in a dose-dependent manner at higher concentrations. Furthermore, at a concentration that resulted in significant apoptosis (100 μM), CHOP, which plays a convergent role in ER stress-mediated apoptosis and is regulated by various upstream ER stress signals, was activated and partially contributed to the DBP-induced apoptosis. However, inhibition of ER stress by 4-PBA, a chemical with chaperone-like activities, augmented the GC-2 cell apoptosis induced by DBP. Further experiments demonstrated that DBP-induced ER stress additionally had a protective role, mediated through the activation of autophagy. These results were confirmed in prepubertal rat testis germ cells; DBP treatment significantly induced testicular atrophy, accompanied by apoptosis, ER stress, and autophagy. Inhibition of ER stress and autophagy significantly aggravated the DBP-induced damage to the germ cells and testes. Taken together, our data suggest that DBP-induced ER stress in germ cells has a cytoprotective effect that is mediated through autophagy activation. These findings provide novel clues regarding the molecular events involved in DBP-induced germ cell apoptosis.